2007
DOI: 10.1111/j.1536-7150.2007.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Sect Effect” in Charitable Giving: Distinctive Realities of Exclusively Religious Charitable Givers

Abstract: An examination of the charitable giving behavior of 16,442 households reveals intriguing patterns consistent with the clubtheoretic approach to religious sect affiliation. The club-theoretic model suggests that individuals with lower socioeconomic standing will rationally be more likely to align themselves with exclusivistic sects. Because sect affiliation is also associated with more obligatory religious contributions, this approach generates novel predictions not anticipated by standard economic models of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
3
27
1
1
Order By: Relevance
“…As found elsewhere, being married has a significantly positive effect on the amount of money donated, again corroborating existing studies (e.g., James & Sharpe, 2007). The impact of being married does not matter much across religious and secular giving.…”
Section: Demographics: Age Education Gender Marital Status and Hosupporting
confidence: 79%
See 1 more Smart Citation
“…As found elsewhere, being married has a significantly positive effect on the amount of money donated, again corroborating existing studies (e.g., James & Sharpe, 2007). The impact of being married does not matter much across religious and secular giving.…”
Section: Demographics: Age Education Gender Marital Status and Hosupporting
confidence: 79%
“…A rich literature exists on religiosity and giving: sometimes religious denominations are included as independent variables (e.g., Bekkers & Schuyt, 2008;Hill & Vaidyanathan, 2011); other times, the data are parsed by a measure of religiosity or religious giving, and these define dependent variables (e.g., Bekkers & Schuyt, 2008;Felstein, 1975;James & Sharpe, 2007;Kitchen, 1992;Wiepking, 2007). In addition to estimating models (1) and (2) using the entire sample, we split the sample into religious giving (time and money) and non-religious (secular) giving of time and money as well.…”
Section: Methodsmentioning
confidence: 99%
“…Showers, Showers, Beggs, and Cox Jr. (2011) showed that religious giving and educational giving could coexist and need not be substitutes. However, James and Sharpe (2007) caution against treating charitable giving to religious and secular purposes on the same footing (that is, as a homogenous activity).…”
Section: Discussionmentioning
confidence: 97%
“…Further, as children's income rose, the propensity for decedents to leave charitable bequests also increased (Auten & Joulfaian, 1996). Bequests to religious organizations have been particularly wealth inelastic (Barthold & Plotnick, 1984), which corresponds to findings of relative income inelasticity in current religious giving (James & Sharpe, 2007a).…”
Section: Literature Reviewmentioning
confidence: 90%